Clinical Characteristics, Etiology, and Initial Management Strategy of Newly Diagnosed Periprosthetic Joint Infection: A Multicenter, Prospective Observational Cohort Study of 783 Patients. (14th May 2020) - Manning, Laurens; Metcalf, Sarah; Clark, Benjamin; Robinson, James Owen; Huggan, Paul; Luey, Chris; McBride, Stephen; Aboltins, Craig; Nelson, Renjy; Campbell, David; Solomon, Lucian Bogdan; Schneider, Kellie; et al.
Abstract: Background: Periprosthetic joint infection (PJI) is a devastating complication of joint replacement surgery. Most observational studies of PJI are retrospective or single-center, and reported management approaches and outcomes vary widely. We hypothesized that there would be substantial heterogeneity in PJI management and that most PJIs would present as late acute infections occurring as a consequence of bloodstream infections. Methods: The Prosthetic joint Infection in Australia and New Zealand, Observational (PIANO) study is a prospective study at 27 hospitals. From July 2014 through December 2017, we enrolled all adults with a newly diagnosed PJI of a large joint. We collected data on demographics, microbiology, and surgical and antibiotic management over the first 3 months postpresentation. Results: We enrolled 783 patients (427 knee, 323 hip, 25 shoulder, 6 elbow, and 2 ankle). The mode of presentation was late acute (>30 days postimplantation and <7 days of symptoms; 351, 45%), followed by early (≤30 days postimplantation; 196, 25%) and chronic (>30 days postimplantation with ≥30 days of symptoms; 148, 19%). Debridement, antibiotics, irrigation, and implant retention constituted the commonest initial management approach (565, 72%), but debridement was moderate or less in 142 (25%) and the polyethylene liner was not exchanged in 104 (23%). Conclusions: In contrast to most studies, late acute infection was the most common mode of presentation, likely reflecting hematogenous seeding. Management was heterogeneous, reflecting the poor evidence base and the need for randomized controlled trials. Abstract : We enrolled 783 patients in a prospective, observational binational study of peri-prosthetic joint infection. Late, acute infections were the commonest mode of presentation. Microbiological causes differed according to affected joint and the timing of the infection. Management approaches were heterogeneous.